R E V I E W: Acacia nilotica (L.) Willd. ex Del. and Problematical in Baluran National Park, East Java - DJUFRI DJUFRI (Biodiversitas Journal of Biological Diversity, 2004)
Acacia nilotica (L.) Del. is a thorny wattle native in India, Pakistan and much of Africa. This acacia is widely distributed in tropical and subtropical Africa from Agypt and Mauritania to South Africa. In Africa and the Indian Subcontinent, Acacianilotica is extensively used as browse, timber and fire-wood species. The bark and seeds are used as source of tannins.The species is olso used for medicinal purposes. Bark of Acacia nilotica has been used for treathing haemorrhages, colds, diarrhoea, tuberculosis and leprosy; while the roots have been used as an aphrodisiac and the flowers for treathing syphillis lessions. The invasion of Acacia nilotica has resulted in the reduction of savanna in Baluran National Park reaching about 50%. Pressure to the savanna has a great impact on the balance and preservation of whole ecosystem in Baluran.Â© 2004 Jurusan Biologi FMIPA UNS SurakartaKey words: Acacia nilotica, biology, ecology, grassland, Baluran National Park.